Clifford, the big red dog - Bridwell, Norman (New York : Scholastic, 1985)
Emily Elizabeth describes the activities she enjoys with her very big, very red dog and how they take care of each other.
Elem. School Library Collection.
2.0
K-3
Keywords: Clifford (Fictitious character : Bridwell) -- Fiction; Dogs -- Fiction; Clifford (Fictional character : Bridwell) -- Fiction; Dogs -- Fiction